Exploring Teachers’ Strategies for Enhancing Student English Speaking: Challenges, Successes, and Classroom Implementation - Dandi Hermawan; Edy Suseno (Jurnal Pendidikan dan Sastra Inggris, 2026)
This qualitative study used Interpretive Phenomenological Analysis of twelve English language teachers’ experiences to examine the challenges and successes of implementing structured speaking strategies. The core finding is that the primary barrier to increasing student English use is affective, stemming from the fear of judgment and cognitive overload during spontaneous tasks, which collectively create a "silent classroom." Success was uniformly linked to two key themes: the Efficacy of Structured Preparation, which acts as an essential cognitive and confidence scaffold through systematic vocabulary work and rehearsal; and the Pivotal Role of Targeted Feedback, delivered in a balanced manner to address both linguistic accuracy and affective concerns. This evidence validates a pedagogical approach where emotional safety and preparation mastery are prerequisites for successful L2 output, enabling a transition toward more frequent, higher-quality English production. The results offer a practical, evidence-based roadmap for L2 speaking instruction. Teachers can confidently adopt structured preparation techniques to manage student anxiety and cognitive load, and can refine their assessment by implementing a system of specific, constructive written feedback that actively supports student confidence rather than inducing fear, thus maximizing engagement and fluency growth. The study provides rich, context-specific data that strengthens the argument that non-linguistic factors are central to L2 speaking success. It provides clear thematic categories for future quantitative model development and sets the stage for complementary qualitative studies focusing on the students’ lived experience of using such structured procedures